Case Study: HarassMap - Cameron Neylon (Research Ideas and Outcomes, 2017)
HarassMap is an NGO based in Cairo that collects and maps crowdsourced data on sexual harassment in Egypt. Alongside this crowd-sourced data gathering it also offers training, workshops and advocacy programs, working with relevant parties to reduce the acceptability of all forms of sexual harassment. The project has been running since 2010 based on the Ushaidi platform. Over this time it has collected a very large number of mapped events reported largely by anonymous members of the public. The data has value both in terms of its richness; mapping data, category of harassment and descriptions are all recorded; and also as a longitudinal dataset that can inform on the success of interventions as well as the development of new forms of harassment. The project has been approached in the past by a number of researchers interested in using the data it has collected. The interest from HarassMap in Pilot Project participation was originally to obtain technical support to address how best to share data. While some technical advice was offered the focus on practice and planning was still useful. Identifying what data resources the project had, and in what form, allowed them to develop an online portal through which data can be made available to researchers on request.